Setif Public Museum and managing its audience’s impressions via its official Facebook page ; an netnographic Study - خالدي الشريف; لونيس باديس (International Journal of Social Communication, 2022)
The research aims to reveal how the Setif Public Museum manages its audience's impressions via its official Facebook page based on the approach of quantitative Netnography and the research found that museums as communication and cultural institutions have adopted digital marketing and virtual presentation of themselves in order to make good impressions for their audiences, These impressions that the Setif National Public Museum was able to positively manage with texts, avatars, videos and interactive comments via its official Facebook page.